SECTORAL FINANCING CONCENTRATION AND SHARIA RURAL BANKS’ PROFITABILITY - Widarjono, Agus; Mifrahi, Mustika (Universitas Airlangga, 2024)
Introduction: Sharia rural banks (SRBs) in Indonesia face high non-performing financing (NPF). The high NPF likely causes a decrease in the profitability of SRBs. One strategy to overcome high financing risk is selecting the appropriate financing strategy either sectoral financing diversification or concentration. This study explores the impact of sectoral financing concentration along with some control variables on the profitability of Sharia rural banks in Indonesia using aggregate data of SRBs from 2010:M1 to 2023:M12 Methods: Our study employs the quantitative method utilizing the Autoregressive Distributed Lag (ARDL). Returns on Assets (ROA) are utilized to measure profitability and Sectoral financing concentration is measured by the Herfindahl-Hirschman index (HHI). Some control variables are assets, capital adequacy ratio (CAR), financing (FIN), cost-income ratio (CIR), NPF, consumer price index (CPI), and COVID. Results: The results show cointegration, indicating the long-run relationship among the variables being studied. The findings signify that sectoral financing concentration fortifies Sharia rural banks' profitability. Also, the size and equity enhance profitability. The results also highlight that low inflation increases profitability and COVID-19 lowers profitability. Conclusion and suggestion: Our results suggest that Sharia rural banks should have competent experts in specific economic sectors such as trade, restaurants, and hotels, which generate more profit due to comparative advantage.